THE EFFECT OF LOCUS OF CONTROL AND SELF-CONCEPT ON THE CAREER MATURITY OF VOCATIONAL HIGH SCHOOL TEACHERS MAJORS ACCOUNTING DEPARTMENT IN EAST JAKARTA - Maulidya, Antika; Zulaihati, Sri; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the impact of locus of control and self-concept on the career maturity ofteacher by using empirical data that is valid and reliable. The method used is a quantitative method.The affirdable population of the study was 89 accounting teacher in east Jakarta. Samples use wereas many as 73 teachers using simple random sampling techniques. Data collection using aquestionnaire instrument with Likert scale. The data analysis technique used is the requirements analysistest, analysis of the regression quation, hypothesis testing, analysis of multiple correlation coefficients,and determination coefficient test. The results of data analysis showed that the data used were normallydistributed and linear. The results of coefficient of determination show that the percentage of locus ofcontrol variables and self-concept to explain career maturity variables simultaneously is 35%.Simultaneously, the result of this study indicate that there is a significant impact of locus of control andself-concept on career maturity. Partially, there is a positive and significant impact of locus of control oncareer maturity, and also the is a positive and significant impact of self-concept on career maturity.